The role of computational thinking in introductory computer science - Gouws, Lindsey Ann (Rhodes University, Faculty of Science, Department of Computer Science, 2014)
Computational thinking (CT) is gaining recognition as an important skill for students, both in computer science and other disciplines. Although there has been much focus on this field in recent years, it is rarely taught as a formal course, and there is little consensus on what exactly CT entails and how to teach and evaluate it. This research addresses the lack of resources for integrating CT into the introductory computer science curriculum. The question that we aim to answer is whether CT can be evaluated in a meaningful way. A CT framework that outlines the skills and techniques comprising CT and describes the nature of student engagement was developed; this is used as the basis for this research. An assessment (CT test) was then created to gauge the ability of incoming students, and a CT-specfic computer game was developed based on the analysis of an existing game. A set of problem solving strategies and practice activities were then recommended based on criteria defined in the framework. The results revealed that the CT abilities of first year university students are relatively poor, but that the students' scores for the CT test could be used as a predictor for their future success in computer science courses. The framework developed for this research proved successful when applied to the test, computer game evaluation, and classification of strategies and activities. Through this research, we established that CT is a skill that first year computer science students are lacking, and that using CT exercises alongside traditional programming instruction can improve students' learning experiences.
Keywords: Computer science; Computational complexity; Problem solving -- Study and teaching